2022
DOI: 10.3390/jcm11143936
|View full text |Cite
|
Sign up to set email alerts
|

Retromode Imaging Modality of Epiretinal Membranes

Abstract: (1) Purpose: To determine the characteristics of macular epiretinal membranes (ERM) using non-invasive retromode imaging (RMI) and to compare retromode images with those acquired via fundus autofluorescence (FAF) and fundus photography. (2) Methods: Prospective observational case-series study including patients with macular ERM with no other ocular disease affecting their morphology and/or imaging quality. We compared RMI, FAF and fundus photography features by cropping and overlapping images to obtain topogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…To integrate the information supplied by conventional techniques, retromode imaging has been introduced in several retinal diseases, such as full-thickness macular holes, epi-retinal membranes, and macular edema due to polypoid choroidal vasculopathy, myopic retinoschisis, and subretinal drusenoid deposits, to provide topographic information on RPE alterations [ 16 , 17 , 18 , 19 , 20 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…To integrate the information supplied by conventional techniques, retromode imaging has been introduced in several retinal diseases, such as full-thickness macular holes, epi-retinal membranes, and macular edema due to polypoid choroidal vasculopathy, myopic retinoschisis, and subretinal drusenoid deposits, to provide topographic information on RPE alterations [ 16 , 17 , 18 , 19 , 20 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Optical coherence tomography (OCT) is a noninvasive imaging modality based on low-coherence interferometry that provides an in vivo cross-sectional view of biological tissues due to their property of reflecting and backscattering light [ 1 , 2 , 3 ]. Nowadays, it is used in several specialties such as ophthalmology, cardiology, otology, and dermatology [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation and management of vitreoretinal interface diseases have particularly benefited from these imaging techniques, which allow for detailed structural analysis of the retinal tissues and the identification of multiple anatomical findings for classification [43,44], differential diagnosis [45][46][47], surgical planning [48][49][50], prognosis [45,49,51], and long-term monitoring [50,52]. It has been recently suggested that retromode imaging modalities, which rely on confocal scanning laser ophthalmoscopic technology, may be a promising additional tool for the assessment of ERMs [53].…”
mentioning
confidence: 99%